Difference in the effects of switching from Candesartan to Olmesartan or Telmisartan to Olmesartan in hypertensive patients with type 2 diabetes: the COTO study - Daikuhara H; Fukunaga K; Ohshima T (Dove Medical Press, 2014)
Hiroyuki Daikuhara, Kensaku Fukunaga, Tomie Ohshima Department of Internal Medicine, Sakaide City Hospital, Kagawa, Japan Purpose: This open-label controlled study compared the therapeutic efficacy of three representative angiotensin II receptor blockers (ARBs) in hypertensive patients with type 2 diabetes attending a hospital outpatient clinic. The primary measure in this study was morning home blood pressure (BP). Patients and methods: Two studies were done concurrently to investigate the effects of switching from two different ARBs to olmesartan. Patients prescribed candesartan (8 mg once daily in the morning) or telmisartan (40 mg once daily in the morning) for 16 weeks were switched to olmesartan (20 mg once daily in the morning) for 16 weeks. Then, they were switched back to candesartan (CO group) or telmisartan (TO group) for another 16 weeks. Results: Data from all patients in the CO group (n=165) and the TO group (n=152) were analyzed. Clinic and morning home BP and urinary albumin levels showed a significant decrease from baseline at 16 weeks after switching to olmesartan in both the CO and the TO group (clinic BP, morning home diastolic BP, and urinary albumin, P<0.05; morning home systolic BP, P<0.01). In contrast, clinic BP, morning home BP, and urinary albumin were significantly increased again 16 weeks after switching back to candesartan or telmisartan (clinic BP, morning home diastolic BP, and urinary albumin, P<0.05; morning home systolic BP, P<0.01). No subjects experienced an adverse reaction that required withdrawal from the study. No adverse reactions attributable to the study drugs were observed. Conclusion: Olmesartan is a promising ARB for BP control in hypertensive type 2 diabetics. Keywords: type 2 diabetes, morning home blood pressure, albuminuria, olmesartan